FAKTOR INTERNAL YANG MEMPENGARUHI HARGA SAHAM PERUSAHAAN YANG TERDAFTAR DI STOCK EXCHANGE OF THAILAND - Rofidatul Hasanah (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2022)
This study aims to influence the company's internal factors such as profitability (ROE), liquidity (QR), leverage (DA), earnings per share, and company size on prices in food and beverage companies listed on the Stock Exchange of Thailand (SET) in the period 2013 – 2017. The population in this study were all food and beverages companies listed on the Stock Exchange of Thailand (SET) as many as 38 companies were included in IPO companies. The sampling technique used in this study is a purposive sampling technique with a sample of 16 companies that meet the criteria. The results of this study indicate that only the earning per share variable has a significant effect on stock prices. While other variables, both profitability, liquidity, leverage, and company size have no significant effect on stock prices.